“I lived only in one, favourite. She died! I lost everything” — on love and death in Orpheus’s Griefs over Euridice written by Franciszek Dionizy Kniaźnin - Prokopczyk, Beata (Wzniosłość i makabra w literackich obrazach śmierci, 2014)
The subject deliberated upon in the present paper is the motive of death as presented in Żale Orfeuszanad Eurydyką funeral series by Franciszek Dionizy Kniaźnin. The collection in question originated ina tragic event in the life of Franciszek Zabłocki, Kniaźnin’s friend, whose beloved wife Katarzyna passedaway shortly after the couple had married. Deeply moved by the young widower’s experiences, Kniaźnindedicated the aforementioned series to Zabłocki, as he described, against the background of the Orpheusand Eurydice myth, the intermingling of the couple’s great love and death. The chief focus of the paperis on the strategies of approaching the theme of death, on how it is presented and perceived, as well ason the emotions it evokes. In Żale Orfeusza…, death, on the one hand, is shown from the perspective ofa devastated individual, and on the other, through references to the popular myth and Jan Kochanowski’sLamentations (Treny), placed within a wider cultural and literary context which indicates universality.